Por uma organização autônoma do proletariado: sindicatos de ofício e os trabalhadores em São Paulo (1917-1930) - Bello Junior, Demetrio Quiros [UNIFESP] (2019)
Our work has as object of study the work of trade unions in the city of São Paulo between 1917 and 1930. As we tried to demonstrate during the research, trade unionism had a strong associative tradition in São Paulo from the first years of the twentieth century and after a period of decline in its activities, experienced a strong recovery during and after the events of the June- July 1917 general strike, with the reconstitution of the old and the formation of new trade unions, as well as the reactivation of the Workers' Federation of São Paulo (FOSP), the body responsible for grouping and coordinating actions in conjunction with these associations. Broadly speaking, these unions were characterized by their autonomy in the labor movement, rejecting ties with the state or political parties. Based on this configuration, our research seeks to understand and analyze how trade union autonomy was conceived and practiced by these unions, noting also the debates about new ways of working and models of organization during the 1920s, since these unions were not exempt from internal differences. Our analysis also contemplates the relations of the trade unions with the governments and with the business, the points of struggle and negotiation, the struggle for rights and the fulfillment of those conquered by the workers. The work with one of the sources mobilized in this dissertation - the records of the union of cobblers and workers supervised by the DEOPS – allowed us to deepen the analysis by observing the dynamics between possibilities and limitations of the individual action within the unions, as well as to problematize on how it was given police surveillance of these people and also to enter one of the most powerful and representative trade unions in the labor movement in São Paulo in the first decades of the twentieth century, the Union of Shoemakers, the shoemakers' union. This reduction of scale also helps us to understand the dynamics, tensions, debates and struggles experienced by the unions in São Paulo during the First Republic.